Aktivitas Antibakteri Ekstrak Daun Jarak Pagar (Jatropha Curcas L) Terhadap Staphylococcus Epidermidis Dan Staphylococcus Aureus Secara In Vitro - Susilo Yulianto; Sunarmi Sunarmi (Poltekkes Kemenkes Surakarta, 2018)
Abstract: Jatropha Leaves, Staphylococcus Epidermidis, Staphylococcus Aureus. Jatropha curcas L leaves contain tannins, saponins and flavonoids. According to some studies, tannins, saponins and flavonoids have antibacterial power. Based on these indications, it is important to do research on antibacterial potency of jatropha leaf extract (Jatropha curcas L) against Staphylococcus epidermidis and Staphylococcus aureus bacteria. The aim of this research is to know Antibacterial Activity of Jatropha curcas L Extract on Staphylococcus epidermidis and Staphylococcus aureus